Lipase catalyzed modification of milkfat - Balcão, Victor M. (1998)
Decreasing consumption of high fat milk and dairy products is driving the dairy industry to seek other uses for increasing surplus of milkfat. Enzyme catalyzed modification of milkfat using lipases is receiving particular attention. This review examines lipase-mediated modification of milkfat. Especial attention is given to industrial applications of lipases for producing structured and modified milkfat for improved physical properties and digestibility, reduced caloric value, and flavor enhancement. Features associated with reactions such as hydrolysis, transesterification, alcoholysis and acidolysis are presented with emphasis on industrial feasibility, marketability and environmental concerns. Future prospects for enzyme catalyzed modification of milk fat are discussed.